Assessment of Physicochemical Characteristics of Produced Water from Terminals of Some Oil Industry Facilities in Nigeria - CC Obunwo; C Chukwudi (Journal of Applied Sciences and Environmental Management)
This study evaluated the physico-chemical characteristics, total hydrocarbon concentration (THC) and some heavy metal levels of produced water from terminals of two oil industry facilities in Nigeria, using standard methods. Appropriate sample bottles were used in the collection of samples for analyses of BOD, other  physico-chemical characteristics, total hydrocarbon and heavy metals. The samples were preserved accordingly and transported to the laboratory in ice - packed coolers. The levels of the physico-chemical properties of produced water in the two locations, showed that mean temperature, pH, TDS, TSS, salinity and turbidity levels were: 24.40± 0.35oC – 25.50 ± 0.35oC; 7.49 ± 0.28 – 7.89 ± 0.30; 8428 ±2332mg/l – 9205 ± 2100mg/l; 8.50 ± 3.40mg/l – 14.30 ± 5.10mg/l; 6108± 1250mg/l – 7422 ± 2280mg/l and 16.00 ± 5.00 NTU – 37.00 ± 9.60 NTU respectively. DO and BOD levels were respectively 3.07 ± 0.40mg/l – 3.29 ± 0.40mg/l and 1.46 ± 0.38mg/l – 1.72 ± 0.48mg/l. COD levels did not vary between the two locations. Mean TOC levels ranged between 0.05 ± 0.02mg/l and 0.06 ± 0.02mg/l while mean THC ranged between 4.72 ± 1.59mg/l and 36.90 ± 3.03mg/l. The levels of the nutrient characteristics of nitrate, phosphate and sulphate ranged as  follows: NO3 - (1.90 ± 1.16mg/l – 2.50 ± 0.26mg/l); PO4 3- (0.52 ± 0.12mg/l – 1.07 ± 0.12mg/l) and SO4 2- (14.40 ± 4.57mg/l – 21.70 ± 2.75mg/l). Levels of trace metals ( Pb, Ni, V, Cd, Hg and Cr) were below detection limits. However, the concentration of Fe ranged between 0.53 ± 0.11mg/l 1.06 ± 0.26mg/l. With the exception of salinity, TDS and TSS, the levels of other physico- chemical characteristics including the trace metals were within the permissible limits set out by Nigeria’s Department of Petroleum Resources (DPR).